Gemeentestichting en contextualisatie in Nederland - Vellekoop, Martijn (Religie & Samenleving, 2009)
The Dutch society is changing fundamentally. The transition to postmodernism and the marginalization of the church mean that a new context is emerging. There is growing interest in church planting within this new context, also from some of the larger denominations in the Netherlands. Nevertheless there hasn’t been done much factual research on church planting. The central question in this research is: “What is the nature and size of church planting in The Netherlands and what is the role of contextualization?” I have been looking for church plants from 1990 and onwards, and I have excluded church plants that originated out of conflicts, or mergers from my research. Migrant churches were also excluded. In the end I found 281 church plants, although the real numbers will be higher (estimated between 300 and 500). Approximately 60% of the church plants have an Evangelical or Pentecostal background. This research gives indications that contextualization is not a big issue for most church planters. Though reaching people with the Gospel is the most important motive for church planters, there are several indications that in practice it’s quite hard to be missional. This supposed lack of a missional practice and attitude needs further research.